2014
DOI: 10.1007/s10162-014-0444-1
|View full text |Cite
|
Sign up to set email alerts
|

Use of Amplitude Modulation Cues Recovered from Frequency Modulation for Cochlear Implant Users When Original Speech Cues Are Severely Degraded

Abstract: Won et al. (J Acoust Soc Am 132:1113-1119, 2012 reported that cochlear implant (CI) speech processors generate amplitude-modulation (AM) cues recovered from broadband speech frequency modulation (FM) and that CI users can use these cues for speech identification in quiet. The present study was designed to extend this finding for a wide range of listening conditions, where the original speech cues were severely degraded by manipulating either the acoustic signals or the speech processor. The manipulation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Likewise, if CI users are programmed with a sixteen-channel sound coding strategies, the bandwidth of the digital filters is approximately two times wider than the bandwidth of the normal auditory filters. Nevertheless, recent studies [ 37 , 46 ] have demonstrated that CI users can make efficient use of AM cues recovered from speech FM cues both in quiet and in challenging listening environments, despite poor frequency selectivity. Therefore, significant correlations found in the current study between STM detection thresholds and sentence identification performance provide a further evidence that the sensitivity to AM cues recovered from broadband FM signals may be an important factor contributing to speech perception capabilities for CI users.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, if CI users are programmed with a sixteen-channel sound coding strategies, the bandwidth of the digital filters is approximately two times wider than the bandwidth of the normal auditory filters. Nevertheless, recent studies [ 37 , 46 ] have demonstrated that CI users can make efficient use of AM cues recovered from speech FM cues both in quiet and in challenging listening environments, despite poor frequency selectivity. Therefore, significant correlations found in the current study between STM detection thresholds and sentence identification performance provide a further evidence that the sensitivity to AM cues recovered from broadband FM signals may be an important factor contributing to speech perception capabilities for CI users.…”
Section: Discussionmentioning
confidence: 99%
“…This point is timely important because CI manufacturers and investigators are making efforts to better represent the acoustic FM information through biphasic pulsatile stimulation strategies. Won et al (2014) [ 46 ] demonstrated that the ability of CI users to use recovered AM cues from broadband FM speech cues plays an important role in speech perception for acoustic environments where original speech cues are severely distorted. In this regard, it is noteworthy that a measure of sentence identification in steady-state background noise was used in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…In NH listeners, it is known that performance is substantially higher for TFS cues derived from a broadband filter than for TFS cues derived from narrow band filters that encompass the same overall frequency range (Smith et al, 2002;Swaminathan and Heinz, 2012;L eger et al, 2015). This result suggests that the processing of both narrowband TFS cues themselves as well as RENVs may play a role in the effective use of TFS components of speech, which has been suggested to contribute to robust speech perception (Swaminathan, 2010;Shamma and Lorenzi, 2013;Won et al, 2012;Won et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The CI does not process this FM information as such, but rather, via filtering. The frequency changing across filters converts the information to amplitude modulations (Won et al 2012; Won et al 2014b). Therefore, in CI users, the Schroeder-phase test evaluates the ability of CI users to hear rapid changes in the spatial distribution of electrical stimulation (Drennan.…”
Section: Introductionmentioning
confidence: 99%